Localized Connectivity in Obsessive-Compulsive Disorder: An Investigation Combining Univariate and Multivariate Pattern Analyses - Hu, Xinyu; Zhang, Lianqing; Bu, Xuan; Li, Hailong; Li, Bin; Tang, Wanjie; Lu, Lu; Hu, Xiaoxiao; Tang, Shi; Gao, Yingxue; Yang, Yanchun; Roberts, Neil; et al. (Frontiers in Behavioral Neuroscience, 2019)
Recent advances in functional magnetic resonance imaging (fMRI) have facilitated the pathophysiology model of obsessive-compulsive disorder (OCD) that encompass a specific network of cortico-striato-thalamo-cortical regions. However, the alterations of localized connectivity in OCD remains to be fully characterized. In the current study, we aimed to apply both univariate analysis and multivariate pattern analysis (MVPA) approach to evaluate the abnormalities of localized connectivity in a relatively large sample of medication-free patients with OCD. A total of 88 OCD patients and 88 healthy control subjects (HCS) underwent resting-state fMRI scans in a 3.0 T scanner. Firstly, we adopted a voxel-wise approach known as Regional Homogeneity (ReHo) analysis, which measures the localized connectivity to characterize regional brain dysfunction. Subsequently, we utilized MVPA technique known as support vector machine (SVM) to examine whether ReHo could be further used to distinguish OCD patients from HCS at the individual level. Relative to HCS, OCD patients showed lower ReHo in bilateral cerebellum and higher ReHo in bilateral superior frontal gyri (SFG), right inferior parietal gyrus and precuneus (P < 0.05, family wise error correction). ReHo value in the left SFG positively correlated with Yale-Brown Obsessive Compulsive Scale total score (r = 0.241, P = 0.024) and obsessive subscale (r = 0.224, P = 0.036). The SVM classification regarding ReHo yielded an accuracy of 78.98% (sensitivity = 78.41%, specificity = 79.55%) with P < 0.001 after permutation testing. The most discriminative regions contributing to the SVM classification were mainly located in frontal, temporal, parietal regions as well as cerebellum while the right orbital frontal cortex was identified with the highest discriminative power. Our findings not only suggested the activation disequilibrium between the prefrontal cortex and the cerebellum appeared to be associated with the pathophysiology of OCD but also indicated the translational role of the localized connectivity as a potential discriminative pattern to detect OCD at the individual level.